Effects of Genetic Strain and Protein Concentrate Removal from Finisher Ration on Performance and Carcass Parameters of Broilers Reared under Hot Climate - Razuki , Waleed M.; Farhan, Sami H.; Jasim, Faris H.; AlKhilani, Firas M.H.; Jameel, Firas R. (International Journal of Poultry Science, 2015)
The present study was carried out during summer season to examine the response of two broilers strains (RS = Ross 308 and CB = Cobb 500) to protein concentrate removal from finisher diet (28-42 d of age) on performance and carcass parameters. On day 28 of age, a total of 960 birds of two strains were randomly assigned on 32 replicates (16 replicates for each strains) of 30 chicks per replicate. Each replicate consist of 15 males and 15 females for each strain which was distinguished by phenotype. Tow finisher dietary treatments were: (1) the basal diet with protein concentrate supplementation; (2) the basal diet without protein concentrate supplementation were fed for both strains. Body weight (BW) and gain (BWG), feed consumption, feed conversion ratio, mortality and carcass parameters were examined. Results showed that the RS strain achieved greater BW, weight gain and feed consumption than CB strain. While, feed conversion ratio and mortality was not affected by strain. Regardless of strain, results showed that removal of protein concentrate (PC) from finisher ration caused reduction in BW at 35 days and 42 days of age and BWG. The reduction in BWG due to PC removing was 8.15% for 7 days and 18.02% for 14 days. As well as, reduction also occurred in feed consumption and feed conversion ratio from 28 to 42 days of age. In contrast, omitting PC from finisher diets had no effect on carcass yield, breast and thigh meat and abdominal fat pad. In conclusion, the results from this study suggest that 14 days withdrawal of protein concentrate prior marketing have adversely negative effect on performance but not on carcass parameters of both strains of broilers during hot climate.